Toner production method

By using ultra-fine bubble water in the melt kneading step of the toner to improve the microdispersion of the dispersed material, the problems of insufficient pigment dispersion and residue of the pulverizing additive are solved, and the color toning with high color strength and high pulverization properties are achieved agent production.

CN119292018APending Publication Date: 2025-01-10CANON KK
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202410905681.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-10
Filing Date
2024-07-08
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing toner production methods, insufficient dispersion of the pigment leads to poor coloring and hiding power, while residual pulverizing additives affect performance, making it difficult to achieve high coloring and high pulverizing properties at the same time.

Method used

By adding water containing ultrafine bubbles to the melt kneading step, the microdispersion of the dispersed material is improved, and the pulverization property and coloring power of the toner are improved by using a method without pulverization additives.

Benefits of technology

A higher degree of microdispersion between the binder resin and the dispersed material is achieved, the coloring power and pulverization properties of the toner are improved, and the problem of residual pulverization additives is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119292018A_ABST
    Figure CN119292018A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing toner. A toner production method includes: a melt kneading step of melt kneading a mixture A containing a binder resin and a material to be dispersed with respect to the binder resin to obtain a kneaded product, in which the mixture A contains 1.0 to 10.0 parts by mass of water with respect to a total of 100.0 parts by mass of the binder resin and the material to be dispersed, the water contained in the mixture A contains air bubbles containing ultrafine air bubbles having a particle diameter of 1000 nm or less, and the number of ultrafine air bubbles contained in the water contained in the mixture A is 1.0 * 104 or more per milliliter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a method for producing a toner for use in an electrophotographic system, an electrostatic recording system, an electrostatic printing system, and a toner jetting system. Background Art

[0002] In recent years, more and more full-color multifunction printers using an electrophotographic system have been used, and their application in the printing market has been progressing. In the printing market, high speed, high-resolution images, high productivity, and low running costs are required while coping with a wide range of media (paper types). Regarding toners, the coloring power can be improved by improving the dispersibility of the colorant in the toner, and the improvement of image resolution can be achieved by further reducing the particle size of the toner.

[0003] As a general method for producing toner particles, a melt-kneading pulverization method is known. Specifically, this method is a method in which toner components such as a binder resin, a colorant, and a release agent are melt-kneaded, and cooled and solidified, and then the kneaded product is micronized by pulverizing means to obtain toner particles. Then, if necessary, the obtained toner particles are classified according to a desired particle size distribution, and an external additive such as a fluidizing agent is added thereto to produce a toner.

[0004] In order to improve the coloring power of toner, for example, Japanese Patent Application Publication No. 2005-352131, Japanese Patent Application Publication No. 2003-098739 and Japanese Patent Application Publication No. 2002-072554 each propose a technology of kneading a resin, water and a pigment in a melt kneading step of a toner production step to thereby disperse the pigment to improve color reproducibility / coloring power.

[0005] In contrast, in order to reduce the particle size of the toner, finer micronization is required in the step of finely pulverizing the kneaded product. Generally, it is noted that finer pulverization leads to lower productivity. Therefore, efficient pulverizing means or equipment for maintaining production volume and suppressing energy consumption is required. Japanese Patent Application Publication No. 2008-191491 and Japanese Patent Application Publication No. 2015-132645 each propose adding a pulverizing aid to the kneaded product of the toner as a means of making the kneaded product of the toner easy to pulverize, thereby achieving improvement in pulverizing efficiency without any investment in production equipment. Summary of the invention

[0006] In order to improve the coloring power, it is effective to increase the hiding power of the colorant such as a pigment to the medium. However, the pigment dispersibility in the toner particles disclosed in any one of the above-mentioned Japanese Patent Application Publication No. 2005-352131, Japanese Patent Application Publication No. 2003-098739 and Japanese Patent Application Publication No. 2002-072554 is considered to be insufficient to produce a high hiding power and has room for improvement. Therefore, a technology for microdispersing dispersed materials such as pigments to a higher degree for the binder resin is required.

[0007] As in Japanese Patent Application Publication No. 2008-191491 and Japanese Patent Application Publication No. 2015-132645, it is known to include inorganic fine particles or the like as a pulverization aid in a kneaded product of a toner and finely pulverize the resulting product as a means of reducing the particle size of the toner. However, the residue of the pulverization aid in the toner may affect the performance of the toner, so that the pulverization aid cannot be used when it is desired to only reduce the particle size of the toner of the existing formulation.

[0008] The present disclosure relates to a method for producing a toner that allows a dispersed material to be microdispersed to a higher degree relative to a binder resin. For example, the present disclosure relates to a method for producing a toner having excellent tinting power, and a method for producing a toner capable of improving toner pulverizability without any residue of a pulverization aid or the like.

[0009] The present disclosure relates to a method for producing a toner, the method comprising:

[0010] A melt-kneading step of melt-kneading a mixture A comprising a binder resin and a dispersed material relative to the binder resin to obtain a kneaded product, wherein

[0011] The mixture A contains 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed material in total,

[0012] The water contained in the mixture A contains bubbles of ultrafine bubbles having a particle size of not more than 1000 nm, and

[0013] The number of ultrafine bubbles contained in the water contained in mixture A is 1.0×10 4 More than one.

[0014] According to the present disclosure, a method for producing a toner that allows a dispersed material to be microdispersed to a higher degree with respect to a binder resin can be provided. For example, according to the present disclosure, a method for producing a toner having excellent tinting power and a method for producing a toner capable of improving toner pulverizability without any residue of a pulverization aid or the like can be provided. Other features of the present invention will become apparent from the following description of exemplary embodiments with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] [ Figure 1 ] is a schematic diagram of a mechanical crusher. DETAILED DESCRIPTION

[0016] In this specification, unless otherwise specified, the term "from XX to YY" or "XX to YY" indicating a numerical range refers to a numerical range including a lower limit and an upper limit, i.e., an endpoint. In addition, when describing a numerical range in sections, the upper and lower limits of each numerical range can be arbitrarily combined.

[0017] The present disclosure relates to a method for producing a toner, the method comprising:

[0018] A melt-kneading step of melt-kneading a mixture A comprising a binder resin and a dispersed material relative to the binder resin to obtain a kneaded product, wherein

[0019] The mixture A contains 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed material in total,

[0020] The water contained in the mixture A contains bubbles including ultrafine bubbles having a particle size of not more than 1000 nm, and

[0021] The number of ultrafine bubbles contained in the water contained in mixture A is 1.0×10 4 More than one.

[0022] According to the above-mentioned toner production method, the dispersed material can be micro-dispersed to a higher degree relative to the binder resin. Therefore, for example, a method for producing a toner with excellent coloring power can be provided. For example, a method for producing a toner that can improve the pulverizability of the toner without any residue of a pulverizing aid or the like can also be provided. The inventors of the present disclosure believe that the reason is as follows.

[0023] Conventionally, in melt kneading using a heat kneading machine such as a pressure kneading machine, a continuous extruder, etc., a mixture of toner components such as a binder resin, a pigment as a colorant, and a release agent are mixed with each other by being subjected to shearing from the device while the temperature is gradually increased due to heating from the kneading machine; thereby, the mixture forms a kneaded product. At this time, secondary particles of the pigment as a dispersed material relative to the binder resin are depolymerized by shearing from the device, and likewise, the release agent as a dispersed material is crushed by shearing from the device; thereby, the pigment is micro-dispersed in the kneaded product.

[0024] In the present disclosure, water containing bubbles containing ultrafine bubbles (UFB) (hereinafter also referred to as "UFB water") is contained in a mixture A which is a raw material mixture containing a binder resin and a dispersed material relative to the binder resin during melt kneading. By including UFB water in the mixture A, the dispersed material can be microdispersed in the binder resin to a higher degree than when the UFB water is not included. UFB is, for example, a bubble with a size of about several tens of nanometers to 1 μm (1000 nm), which does not move upward but can be stably maintained in water for a long time.

[0025] It can be inferred that the mechanism by which the dispersed material can be highly finely dispersed in melt kneading by including UFB water in the mixture A is as follows. The UFB present in the water can exert a compression failure effect and a surface effect. The compression failure effect is the effect of shrinking the bubbles, rapidly increasing the pressure inside the bubbles, and emitting shock waves when the bubbles disappear when a physical force is applied from the outside. When UFB water is mixed into the raw material mixture A, the UFB is adsorbed on the surfaces of the binder resin and the dispersed material by the surface effect. In addition, it is believed that the shock wave emitted by the compression failure of the UFB caused by shearing during kneading can apply a stronger external force to the dispersed material than in the previous kneading, so that the dispersed material can be efficiently micronized and finely dispersed.

[0026] For example, when a pigment is contained as a dispersed material, it is considered that the pigment is further finely dispersed in the toner, and the hiding power against light is improved; thereby, the color development is improved, and the coloring property is further improved. Therefore, the dispersed material preferably contains a pigment.

[0027] For example, when a release agent is included as a dispersed material, the release agent further microdisperses the kneaded product of the toner component. In the kneaded product, the position where the release agent is present is likely to become a cross section during pulverization. Therefore, in the pulverization step after kneading, the efficiency of pulverization is improved. Therefore, the pulverizability of the toner can be improved without any residue of a pulverization aid or the like. Therefore, the dispersed material preferably includes a release agent.

[0028] In addition, for example, when a pigment and a release agent are included as the dispersed material, the pigment is further finely dispersed in the toner; thereby, the coloring power can be improved. In addition, the fine dispersion of the release agent can improve the pulverizability of the toner. Therefore, the dispersed material preferably includes a pigment and a release agent.

[0029] Through the above mechanism, it can be considered that according to the present disclosure, a method for producing a toner is provided in which the dispersed material is microdispersed to a higher degree relative to the binder resin. The dispersed material is not limited to a pigment or a release agent, as long as it can exert the above-mentioned compression failure effect and surface effect. Examples of the dispersed material include plasticizers, charge control agents, colorants other than pigments; and resin particles and inorganic particles contained inside toner particles.

[0030] First, ultra fine bubble water (UFB water) is described.

[0031] <Ultrafine bubbles>

[0032] Bubbles with a particle size of 100 μm or more (submillimeter bubbles) move upward in water and disappear at the gas-liquid interface. Bubbles with a particle size greater than 1 μm and less than 100 μm (microbubbles) cannot resist water pressure and tend to disappear in water while their rising speed in water decreases. For them, ultrafine bubbles (nanobubbles) with a particle size of no more than 1 μm (1000 nm) can exist stably in water even for months. When producing toners or masterbatches, when extremely fine bubbles such as ultrafine bubbles as described above are contained in the raw material mixture, the dispersibility of the dispersed material can be improved by the compression destruction effect and the surface action.

[0033] The bubbles are preferably composed of at least one gas selected from the group consisting of rare gases, oxygen, nitrogen, carbon dioxide, ozone gas and air. Among them, at least one gas selected from the group consisting of oxygen, nitrogen, carbon dioxide, ozone gas and air is preferred. In particular, the gas constituting the bubbles is preferably air. Air is preferred because in the case of air, the bubble generator does not need to be accompanied by any device (gas generator, storage device such as a gas cylinder).

[0034] In particular, mixture A, which is a mixture of raw materials of toner particles, needs to contain 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed material in total. The water contained in mixture A is UFB water containing bubbles containing the specific UFB described below.

[0035] When the water containing ultrafine bubbles is less than 1.0 parts by mass, the liquid cannot be fully diffused on the surface of the material. Therefore, the points of compression failure become fewer, and the effect of diffusing the dispersed material cannot be fully exerted. On the other hand, when the water containing ultrafine bubbles exceeds 10.0 parts by mass, the amount of water present between the materials is so large that the shear from the kneader is difficult to fully act on the raw materials. Therefore, the dispersion effect of the dispersed material is not improved.

[0036] The content of water is preferably 2.0 to 8.0 parts by mass relative to a total of 100.0 parts by mass of the binder resin and the dispersed material. For example, when the following masterbatch is produced at one time in the process of producing a toner, the raw material mixture may be melt-kneaded multiple times. Generally, it is considered that the contained water evaporates by melt-kneading. Therefore, when the mixture is melt-kneaded multiple times, in each melt-kneading, it is preferred that 1.0 to 10.0 parts by mass of UFB water relative to a total of 100.0 parts by mass of the binder resin and the dispersed material be mixed with the mixture.

[0037] The water contained in the mixture A contains bubbles including ultrafine bubbles having a particle size of not more than 1000 nm. It is necessary that the number of ultrafine bubbles having a particle size of 1000 nm or less contained in the water contained in the mixture A is 1.0×10 4 When the UFB number density is less than 1.0×10 4 When the number density of bubbles is 1.0×10 / ml, the amount of UFB attached to the surface of the dispersed material is insufficient. Therefore, it is considered that the compression failure effect or surface action sufficient to deagglomerate the dispersed material cannot be obtained in the melt kneading. Therefore, it is considered that the dispersed material cannot be microdispersed to a higher degree. Therefore, it is necessary that the number density of bubbles is 1.0×10 / ml. 4 More than 5.0×10 per ml, preferably 5.0×10 6 More than one.

[0038] On the other hand, from the viewpoint of productivity, the UFB number density is preferably 3.0×10 10 The UFB number density is preferably 1.0×10 per ml. 4 ~3.0×10 10 More preferably, 5.0×10 6 ~3.0×10 10 indivual.

[0039] In addition, in the water contained in mixture A, the number average particle diameter of the bubble is preferably below 1000nm. When the number average particle diameter of the bubble contained in the water is not more than 1000nm, the bubble tends to each have a smaller diameter than the diameter causing Brownian motion, and is therefore easy to exist more stably. Therefore, after mixing with the binder resin and the dispersed material until the mixture is put into a kneading machine, bubbles can be more fully present. When the number average particle diameter is within the above range, the contact points of the bubble and the dispersed material surface are more. Therefore, it is believed that it is easy to obtain a more sufficient compression failure effect or surface action for disaggregating the dispersed material. Therefore, it is believed that the dispersed material is easily micro-dispersed to a higher degree.

[0040] Therefore, the number average particle size of the bubbles contained in the added water is preferably 1000 nm or less, more preferably 700 nm or less. The lower limit of the particle size is not particularly limited. The number average particle size of the bubbles is, for example, preferably 10 to 1000 nm, more preferably 50 to 1000 nm, further preferably 10 to 700 nm, further more preferably 50 to 700 nm, and particularly preferably 100 to 700 nm.

[0041] The particle size and number density of UFB were measured by laser diffraction and scattering. The particle size of the bubbles is the number average particle size. The number density of UFB is the ratio of bubbles with a particle size below a specified value to the volume (per milliliter) of water. In the following examples, the particle size of the bubbles was calculated using a nanoparticle size distribution analyzer (trade name: SALD-7500nano, manufactured by Shimadzu Corporation).

[0042] In addition, the number density of UFBs below 1000 nm was calculated using a nanoparticle tracking particle size measuring instrument (trade name: NanoSight NS300, manufactured by Malvern Panalytical) that allows observation of the number of particles by imaging scattered light irradiated by laser light via a camera.

[0043] As a means of producing water containing UFB, as long as it is possible to produce water containing bubbles that meets the required particle size and the required particle concentration, a known method can be used without particular limitation. For example, a known device suitable for producing water containing fine bubbles can be used to produce water containing UFB, such as the fine bubble generating nozzle disclosed in Japanese Patent Application Publication No. 2014-104441; and the fluid mixer disclosed in WO 2009 / 088085. By appropriately setting the use conditions of such a device, water containing bubbles whose particle size distribution is controlled within the desired range can be obtained.

[0044] For example, as disclosed in Japanese Patent Application Publication No. 2019-42732, it is also possible to produce bubbling water by applying thermal energy to a liquid to generate bubbles by film boiling. By appropriately setting conditions such as film boiling, water containing bubbles with a particle size distribution controlled within a desired range can be obtained.

[0045] As disclosed in Japanese Patent Application Publication No. 2022-144980, the UFB number density can be adjusted by placing the UFB water under reduced pressure, thereby removing a portion of the water to concentrate the UFB-containing water. In addition, UFB can be prepared using commercially available (researched) bubble-containing water (e.g., "high-density ultrafine bubbles" and "ultra-high-density ultrafine bubbles" (both trade names, manufactured by NANOX CO., LTD.). The masterbatch and toner are produced by adding the obtained UFB to the mixture A in the raw material mixing step before melt kneading.

[0046] Binder resin

[0047] The toner particles contain a binder resin. As the binder resin, a known polymer can be used. Specifically, for example, any of the following polymers can be used: homopolymers of styrene and its substituents, such as polystyrene, polyparachlorostyrene, and polyvinyltoluene; styrene-based copolymers, such as styrene-parachlorostyrene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-acrylate copolymers, styrene-methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, and styrene-acrylonitrile-indene copolymers; polyvinyl chloride, phenolic resins, natural resin-modified phenolic resins, natural resin-modified maleic acid resins, acrylic resins, methacrylate resins, polyvinyl acetate, silicone resins, polyester resins, polyurethane resins, polyamide resins, furan resins, epoxy resins, xylene resins, polyvinyl butyral, terpene resins, coumarone-indene resins or petroleum resins. One of these resins can be used alone, or two or more of these resins can be used in combination.

[0048] Among them, amorphous polyester resin is preferred. The amorphous polyester resin used here is preferably a condensation product of a carboxylic acid component and an alcohol component. As the carboxylic acid component and the alcohol component used in this article, known ones can be used. The carboxylic acid component preferably includes at least one selected from the group consisting of terephthalic acid and fumaric acid. The alcohol component preferably includes an alkylene oxide adduct of bisphenol A (the average addition mole number is preferably 1 to 5 mol). As the acid component, tricarboxylic acids such as trimellitic acid can be used.

[0049] For the binder resin, a polyester resin L having a low softening point and a polyester resin H having a high softening point may be used in combination. The content ratio (L / H) of the polyester resin L having a low softening point and the polyester resin H having a high softening point used herein is, for example, 60 / 40 to 90 / 10 based on mass. Preferably, the softening point of the polyester resin L having a low softening point is 70° C. or more and less than 100° C. Preferably, the softening point of the polyester resin H having a high softening point is 100° C. to 160° C.

[0050] The binder resin may contain a crystalline polyester resin in consideration of compatibility of low temperature fixability and anti-blocking properties. The crystalline polyester resin used here is preferably a polycondensate of an alcohol having an aliphatic diol with a carbon number of 2 to 23 and a carboxylic acid having an aliphatic dicarboxylic acid with a carbon number of 4 to 24.

[0051] The crystalline polyester resin is more preferably a condensation product of the following alcohols and the following carboxylic acids: the content of aliphatic diols having 4 to 12 carbon atoms in the alcohols is 80 mol% to 100 mol% (further preferably 85 mol% to 100 mol%) of the total alcohols constituting the crystalline polyester resin; the content of aliphatic dicarboxylic acids having 4 to 20 carbon atoms in the carboxylic acids is 80 mol% to 100 mol% (further preferably 85 mol% to 100 mol%) of the total carboxylic acids constituting the crystalline polyester resin.

[0052] The aliphatic diol used herein is preferably a linear aliphatic diol, examples of which include 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol, etc. The derivative is not particularly limited as long as the same resin structure is obtained by polycondensation. An example of the derivative is a derivative obtained by esterifying any of the aforementioned diols.

[0053] The aliphatic dicarboxylic acid used herein is preferably a straight-chain aliphatic dicarboxylic acid, examples of which include malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, glutaconic acid, azelaic acid, sebacic acid, hexadecanedioic acid, eicosanedioic acid and derivatives thereof. The derivative is not particularly limited as long as the same resin structure is obtained by polycondensation. Examples of the derivative include anhydrides of any dicarboxylic acid and derivatives obtained by alkyl esterification or chlorination of a dicarboxylic acid component.

[0054] On the other hand, the carboxylic acid may be used in combination with a carboxylic acid other than the above-mentioned aliphatic dicarboxylic acids.

[0055] <Colorant>

[0056] The toner particles may contain a colorant. That is, the dispersed material may contain a colorant, and preferably a pigment. Except for the case of producing the transparent toner described below, a colorant such as a pigment is generally contained. Examples of the pigment used here include known organic pigments, carbon black, and magnetic bodies.

[0057] Examples of cyan pigments as used herein include copper phthalocyanine compounds and derivatives thereof, anthraquinone compounds, and basic dye lake compounds; specifically, CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66.

[0058] Examples of magenta pigments as used herein include condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds and perylene compounds; specifically, CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221 and 254, and CI Pigment Violet 19.

[0059] Examples of the yellow pigment used herein include condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds and allylamide compounds; specifically, CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 191 and 194.

[0060] Examples of the black pigment used herein include carbon black, a magnetic body, and a material color-matched to black using any of the above-mentioned yellow pigment, magenta pigment, and cyan pigment.

[0061] Examples of the white pigment used herein include titanium oxide, magnesium oxide, aluminum oxide, zinc oxide, barium sulfate, calcium carbonate, calcium titanate, strontium titanate, silica, clay, and talc.

[0062] One of the above pigments may be used alone, or two or more thereof may be used in mixture. Preferably, a colorant that can also be used in the form of a solid solution is selected in consideration of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility to toner particles.

[0063] The content of the colorant (pigment) in the mixture A (or the first mixture or the second mixture described below) is preferably 1 to 60 parts by mass, more preferably 1 to 20 parts by mass, and further preferably 5 to 15 parts by mass relative to 100 parts by mass of the binder resin. When producing the following masterbatch, that is, when the mixture A is the first mixture, the content of the colorant is preferably 20 to 60 parts by mass, and more preferably 30 to 55 parts by mass relative to 100 parts by mass of the binder resin.

[0064] When the pigment is any one of cyan, magenta, yellow and black pigments, the content is preferably 1 to 20 parts by mass relative to 100 parts by mass of the binder resin. When the pigment is a white pigment, the content is preferably 20 to 50 parts by mass relative to 100 parts by mass of the binder resin in order to sufficiently cover the primary color for expressing white so that the primary color cannot be recognized.

[0065] An example of a toner that does not contain a pigment or a colorant is a transparent toner used for brightening by fusing the transparent toner on a printing medium. In the case of a transparent toner, as described above, by including a release agent in the toner, the diameter can be easily reduced.

[0066] <Release Agent>

[0067] The toner particles may contain a release agent. That is, the dispersed material may contain a release agent. The following are examples of release agents as used herein:

[0068] Hydrocarbon waxes, such as low molecular weight polyolefins (low molecular weight polyethylene and low molecular weight polypropylene), olefin copolymers, refined ozokerite, paraffin, microcrystalline wax and Fischer-Tropsch wax; silicones having a melting point; fatty acid amides, such as oleamide, erucamide, ricinoleic acid amide, and stearic acid amide; ester waxes, such as stearyl stearate; vegetable waxes, such as carnauba wax, rice wax, candelilla wax, Japan wax and jojoba oil; animal waxes, such as beeswax; mineral and petroleum waxes, for example, montan wax, ozokerite and ester waxes; and modified products thereof.

[0069] As a release agent, one of the above can be used alone, or two or more thereof can be used in combination. The release agent preferably contains hydrocarbon wax. The melting point of the release agent is preferably below 150°C, more preferably 40°C to 130°C, and further preferably 40°C to 110°C. The content of the release agent in the mixture A (or the second mixture described below) is preferably 1 to 30 parts by mass, more preferably 2 to 20 parts by mass, and further preferably 5 to 15 parts by mass relative to 100 parts by mass of the binder resin.

[0070] <Charge Control Agent>

[0071] If necessary, a charge control agent may also be included in the toner. Known charge control agents may be used. In particular, metal compounds of aromatic carboxylic acids that are colorless, provide a fast charging speed for the toner, and can stably maintain a certain charge amount are preferred.

[0072] The following are examples of negative charge control agents: salicylic acid metal compounds, naphthoic acid metal compounds, dicarboxylic acid metal compounds, polymer compounds each having a sulfonic acid or a carboxylic acid in a side chain, polymer compounds each having a sulfonate or a sulfonate ester in a side chain, polymer compounds each having a carboxylate or a carboxylate ester in a side chain, boron compounds, urea compounds, silicon compounds and calixarene.

[0073] Examples of the positive charge control agent as used herein include quaternary ammonium salts, polymer compounds each having any one of quaternary ammonium salts in a side chain, guanidine compounds, and imidazole compounds. The charge control agent may be added internally or externally to toner particles.

[0074] The amount of the charge control agent added is preferably 0.2 parts by mass to 10 parts by mass based on 100 parts by mass of the binder resin.

[0075] <Developer>

[0076] Although the toner can be used as a one-component developer, it is preferably mixed with a magnetic carrier and used as a two-component developer in order to further improve dot reproducibility and because a stable image is obtained over a long period of time.

[0077] As the magnetic carrier used in this article, any of the following known ones can be used: surface oxidized iron powder; unoxidized iron powder; metal particles, alloy particles, and oxide particles of iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, chromium, rare earth, etc.; magnetic bodies such as ferrite; and a magnetic body dispersion resin carrier (so-called resin carrier) comprising a magnetic body and a binder resin for maintaining the magnetic body in a dispersed state.

[0078] Generally, when the toner is mixed with a magnetic carrier and used as a two-component developer, good results are obtained when the mixing ratio of the carrier is preferably 2 mass % to 15 mass %, more preferably 4 mass % to 13 mass %, based on the toner concentration in the two-component developer.

[0079] <Toner Production Method>

[0080] The steps of producing the toner will be described.

[0081] The method for producing the toner is not particularly limited as long as UFB water is contained in the mixture A which is a mixture containing the binder resin and a dispersed material such as a colorant and a releasing agent relative to the binder resin, and as long as the method includes a melt-kneading step of melt-kneading the mixture A to produce a kneaded product. The toner production method preferably includes a pulverizing step of pulverizing the kneaded product obtained in the melt-kneading step.

[0082] For example, the production method of the toner may include: a step of pulverizing the kneaded product so that the resultant has a desired particle size, and then adhering inorganic fine particles to the surface of the toner particles to impart fluidity; and a step of adjusting the circularity of the toner by dispersing throughout an aqueous medium and then heating. The production method of the toner may also include a step of adjusting the circularity of the toner particles by using a heat treatment apparatus as shown in Japanese Patent Application Publication No. 2013-20244.

[0083] <Raw material mixing step>

[0084] In the mixing step of the raw materials, a predetermined amount of a binder resin and a dispersed material relative to the binder resin are weighed and combined, and mixed to produce a mixture. The mixer used here is not particularly limited, and examples thereof include a Henschel mixer (manufactured by Nippon Coke & Engineering Co., Ltd.); Super Mixser (manufactured by Kawata Manufacturing Co., Ltd.); Ribocone (manufactured by Okawara Mfg. Co., Ltd.); Nauta Mixer, Turbulizer, and Cyclomix (manufactured by Hosokawa Micron Corporation); Spiral Pin Mixer (manufactured by Pacific Machinery & Engineering Co., Ltd.); and Mixer (manufactured by Matsubo Corporation).

[0085] <Adding water containing ultrafine bubbles as bubbles>

[0086] As a means for including the ultrafine bubble-containing water in the mixture, water may be added to a mixer together with a binder resin in the step of mixing the raw materials; or water may be added to the mixture mixed in the step of mixing the raw materials, and the resultant may be uniformly mixed again using a mixer, etc. The raw material mixture containing the ultrafine bubble-containing water is defined as mixture 1.

[0087] <Melt-kneading step and cooling step>

[0088] The toner raw material containing the mixture 1 is melt-kneaded using, for example, a twin-screw extruder. In the melt-kneading step, a batch kneader such as a pressure kneader and a Banbury kneader or a continuous kneader can be used. In view of the advantage of continuous production capability, a single-screw or twin-screw extruder is preferred. The melt-kneading temperature is preferably about 100° C. to 200° C.

[0089] <Crushing Step>

[0090] The kneaded product 1 obtained by melt-kneading the mixture 1 is further rolled with two rollers or the like, and cooled, for example, by a cooling step of cooling by water. Then, the kneaded product 1 after cooling is crushed to have a desired particle size in a pulverizing step. For example, in the pulverizing step, first, the kneaded product is coarsely pulverized with a crusher, a hammer mill, a grinding machine, etc. In addition, the obtained product is finely pulverized with a mechanical pulverizer such as Inomiser (manufactured by Hosokawa Micron Corporation), Kryptron (manufactured by Kawasaki Heavy Industries, Ltd.), Super Rotor (manufactured by Nisshin Engineering Inc.), and Turbo Mill (manufactured by Freund-Turbo Corporation) to obtain a finely pulverized product.

[0091] For example, a mechanical pulverizer as shown in the schematic diagram of the accompanying drawings can be used. When a specified amount of a coarsely pulverized product (a pulverized material) is put into the powder supply port (powder input port) 101 of the mechanical pulverizer shown in the accompanying drawings, the coarsely pulverized product that has passed through the spiral shell 102 is introduced into the pulverizing chamber that is the gap between the rotor 103 and the stator 104. Then, the coarsely pulverized product is instantly pulverized by the impact between the rotor 103 rotating at high speed around the pivot 107 in the pulverizing chamber having a large number of grooves on its surface and the stator 104 having a large number of grooves on its surface. Afterwards, the finely pulverized product is discharged from the powder discharge port 106 via the rear chamber 105. The left side of the accompanying drawings is a schematic diagram of a cross section taken along the DD′ line.

[0092] The mechanical pulverizer is provided with a cold air generator 108 for supplying cold air into the device together with the coarsely pulverized product as the pulverized object through the powder supply port 101. The mechanical pulverizer is also provided with a cold water supply port 109 and a cold water discharge port 110 for allowing water to flow into the cooling jacket for controlling the temperature of the device by cold water.

[0093] <Grading steps>

[0094] The classification step here is a step of classifying the finely pulverized product obtained in the pulverization step to produce toner particles having a desired particle distribution.

[0095] As a classifier used for classification, known equipment such as a wind classifier, an inertial classifier, and a screening classifier can be used, and specific examples thereof include Classiel, Micron Classifier, Spedic Classifier (manufactured by Seishin Enterprise Co., Ltd.); Turbo Classifier (manufactured by Nisshin Engineering Inc.); Micron Separator, Turboplex (ATP), and TSP Separator (manufactured by Hosokawa Micron Corporation); Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.); Dispersion Separator (manufactured by Nippon Pneumatic Industry Co., Ltd.); and YM Micro Cut (manufactured by Yaskawa Co., Ltd.).

[0096] The toner particles prepared through the above steps can be used as a toner as they are. If necessary, the toner can be formed by adding inorganic fine particles such as silicon dioxide, aluminum oxide and titanium dioxide, and / or resin fine particles such as vinyl resin, polyester resin and silicone resin to the toner particles in a dry state by applying a shear force. These inorganic fine particles and resin fine particles can be used as external additives such as flow aids and cleaning aids.

[0097] The production method of the toner may include a step of imparting shear stress to the aggregate of the pigment by melt-kneading the pigment with a part of the binder resin using, for example, a twin-screw extruder, and further, wetting the surface of the pigment particles with the binder resin. Through this step, a pigment dispersion (masterbatch) obtained by pre-dispersing the pigment relative to a part of the binder resin can be produced. Next, in the method, a kneading step of diluting and melt-kneading is performed in a manner such that the pigment dispersion has a predetermined pigment concentration, and the obtained pigment dispersion is diluted with the remaining part of the binder resin and any other materials as needed; thereby, a toner can be produced.

[0098] When toner is produced after the above-mentioned masterbatch is produced at one time, insufficient dispersibility of the pigment in the pigment dispersion results in the presence of coarse particles of the pigment having about several microns to ten microns. The coarse particles of the pigment in the pigment dispersion cannot be completely depolymerized even through the continuous steps of dilution and melt kneading, and remain in the toner. The presence of low-resistance components such as coarse particles of the pigment in the toner or on the surface of the toner tends to lead to the progression of charge leakage from the charged toner, and the reduction in the amount of charge may cause the toner to scatter. Therefore, it is required to improve the dispersibility of the pigment and reduce the coarse particles of the pigment in the pigment dispersion more than conventionally.

[0099] Even when the masterbatch is produced at once as described above, it is preferred to contain UFB water in the mixture when the masterbatch is produced by melt kneading. It is believed that the above-mentioned compression failure effect and surface effect are exerted, and the coarse particles of the pigment can be deagglomerated well.

[0100] That is, it is preferred that the melt-kneading step is a first melt-kneading step of melt-kneading a first mixture containing a part of the binder resin and at least a part of the pigment to obtain a first kneaded product, the first mixture being the mixture A. The toner production method includes a second melt-kneading step of melt-kneading a second mixture containing at least the first kneaded product and the remaining binder resin to produce a second kneaded product after the first melt-kneading step.

[0101] Preferably, UFB water is also included in the second mixture, i.e., in the raw material mixture when the remainder of the binder resin and any other materials as needed are melt-kneaded using a masterbatch. UFB water also allows the dispersed material to be well dispersed in the second melt-kneading. The same water as included in mixture A can be used as UFB water here.

[0102] Therefore, it is preferred that the second mixture contains 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed material in the second mixture in total.

[0103] The water contained in the second mixture contains bubbles including ultrafine bubbles having a particle size of 1000 nm or less, and

[0104] The number of ultrafine bubbles with a particle size of 1000 nm or less contained in the water contained in the second mixture is 1.0×10 4 More than one.

[0105] In the second mixture, it is preferred that the number average particle size of the bubbles in water also be within the aforementioned range.

[0106] The weight average particle diameter (D4) of the toner is preferably 3.0 μm to 20.0 μm, more preferably 4.0 μm to 10.0 μm.

[0107] In the mixture A (or the first mixture or the second mixture), the value of the mass ratio (water / dispersed material) of the content of water (UFB water) to the content of the dispersed material is not particularly limited. The value of the ratio (water / dispersed material) is preferably 0.02 to 1.00, more preferably 0.03 to 0.90. The above range can lead to better dispersibility of the dispersed material.

[0108] <Method for measuring weight average particle diameter (D4) of finely pulverized product and toner>

[0109] The weight-average particle diameter (D4) of the finely pulverized product and the colorant (hereinafter referred to as the colorant in this measuring method) is calculated by: measuring in 25,000 effective measurement channels by using a precision particle size distribution measuring instrument "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.) based on the pore resistance method and equipped with a 50 μm aperture tube and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) for setting measurement conditions and analyzing measurement data; and analyzing the measurement data.

[0110] As the aqueous electrolyte solution used for measurement, special grade sodium chloride dissolved in ion exchange water at a concentration of about 1 mass %, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.) can be used.

[0111] Prior to measurement and analysis, the dedicated software was set as follows.

[0112] In the "Screen for Modifying Standard Operating Method (SOM)" of the dedicated software, the total count of the control mode was set to 50,000 particles, the number of measurements was set to 1, and the Kd value was set to the value obtained using "Standard Particles 10.0 μm" (manufactured by Beckman Coulter, Inc.). The threshold and noise level were automatically set by pressing the measurement button of the threshold / noise level. The current was set to 1600 μA, the gain was set to 2, the electrolyte solution was set to ISOTON II, and the rinse port tube after measurement was checked.

[0113] In the "screen for setting pulse to particle size conversion" of the dedicated software, the interval was set to the logarithmic particle size, the particle size interval was set to 256 particle size intervals, and the particle size range was set to 1 μm to 30 μm.

[0114] The specific measurement method is as follows.

[0115] (1) Place approximately 200 mL of the electrolyte aqueous solution in a 250 mL round-bottom glass beaker to be used with the Multisizer 3. Place the beaker in the sample holder and stir it counterclockwise at 24 revolutions per second using a stirring rod. Remove dirt and bubbles from the nozzle using the "Rinse nozzle" function of the dedicated software.

[0116] (2) About 30 mL of the electrolyte aqueous solution was placed in a 100 mL flat-bottom glass beaker. About 0.3 mL of the following diluent was added thereto: the diluent was a dispersant "Contaminon N" (a 10% by mass aqueous solution of a precision measuring instrument cleaning detergent having a neutral pH of 7 composed of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted 3 times by mass with ion exchange water.

[0117] (3) A predetermined amount of ion-exchanged water is placed in a water tank equipped with an ultrasonic disperser "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) having two oscillators with an oscillation frequency of 50 kHz and a phase shift of 180° and an electrical output of 120 W, and about 2 ml of the above-mentioned Contaminon N is added to the water tank.

[0118] (4) Place the beaker described in paragraph (2) into the opening of the beaker holder of the ultrasonic disperser, start the ultrasonic disperser, and adjust the vertical position of the beaker in such a way that the resonance condition of the surface of the aqueous electrolyte solution in the beaker is maximized.

[0119] (5) While ultrasonic irradiation is being applied to the aqueous electrolyte solution in the beaker described in paragraph (4), about 10 mg of the toner is added little by little to the aqueous electrolyte solution to be dispersed. The ultrasonic dispersion is continued for another 60 seconds. For the ultrasonic dispersion, the temperature of the water in the water tank is appropriately adjusted to 10° C. to 40° C.

[0120] (6) The aqueous electrolyte solution in which the toner is dispersed described in paragraph (5) is added dropwise to the round bottom beaker placed in the sample holder described in paragraph (1) using a pipette so that the measurement concentration is about 5%. Then, measurement is performed until the number of particles measured reaches 50,000.

[0121] (7) Use the dedicated software attached to the instrument to analyze the measurement data and calculate the weight average particle size (D4). When the chart / volume % is set in the dedicated software, the "average diameter" on the screen of the analysis / volume statistical value (arithmetic mean) is the weight average particle size (D4).

[0122] Example

[0123] Hereinafter, the present disclosure will be described in more detail by using Examples and Comparative Examples, however, these Examples and Comparative Examples do not limit the present disclosure at all.

[0124] <Measurement of the number average particle size of bubbles and the number density of UFB>

[0125] The number average particle size of the bubbles and the number density of UFBs were measured as follows.

[0126] The average particle size of the bubbles in the prepared UFB water was measured on a number basis using a particle size distribution measurement analyzer (trade name: SALD-7500nano, manufactured by Shimadzu Corporation). At this time, the batch cell (SALD-BC75) of the SALD-7500nano connected to the measuring device was filled with UFB water, and the refractive index value of the particles was set to 1.25 to 0.00i (i is a plural number), and then the measurement was performed. The analysis was performed using the accompanying software (WingSALDII), and the number average particle size in the measurement range of 10nm to 3000nm was calculated.

[0127] The number density of UFB below 1000nm was calculated using a nanoparticle tracking particle size measuring instrument (trade name: NanoSight NS300, manufactured by Malvern Panalytical). UFB water was loaded into the sample chamber of the Nanosight unit and recorded on the video for 60 seconds at a frame rate of 25fps. The movement of the particles was analyzed using the attached software (NTA software version 3.2) to calculate the number density of bubbles from 10nm to 1000nm (per ml).

[0128] For each of UFB waters 1 and 2 described below, a value obtained by multiplying the number density of diluted water obtained by diluting 100 times with pure water by 100 was used as the number density.

[0129] <Preparation of Ultrafine Sparkling Water>

[0130] Each UFB water was prepared by the following method. Table 1 shows the UFB water used in Examples and Comparative Examples.

[0131] (UFB Water 1)

[0132] UFB water 1 is commercially available (research) UFB water (trade name: "High-density ultrafine bubbles", manufactured by NANOX CO., LTD.)

[0133] (UFB water 2 to 4)

[0134] UFB waters 2 to 4 were obtained by diluting UFB water 1 with pure water or concentrating UFB water 1 in vacuo using a rotary evaporator (N-1300E-W manufactured by TOKYO RIKAKIKAI CO., LTD.) to adjust the UFB number density to the values ​​shown in Table 1.

[0135] (UFB Water 5)

[0136] A cycle of the following operation was repeated 5 times: bubbles were contained in pure water using a micro / nano bubble generator (OM4-MDG-05 manufactured by AURATEC CO., LTD.) at 25° C. and 1.8 L / min, and the mixture was allowed to stand for 10 hours. After repeating the above cycle 5 times, the number density of the contained UFB was adjusted by diluting with pure water to obtain UFB water 5.

[0137] (UFB Water 6 and 7)

[0138] UFB water 6 was prepared in the same manner as UFB water 5, except that the number of repetitions of the cycle was 1. UFB water 7 was obtained by further diluting UFB water 6 with pure water to adjust the number density of UFB contained.

[0139] (UFB Water 8)

[0140] The following operation was performed once: using a micro / nano bubble generator (OM4-MDG-05 manufactured by AURATEC), bubbles were contained in pure water at 25° C. and 1.2 L / min. The number density of UFB contained was adjusted by diluting with pure water, and UFB water 8 was obtained.

[0141] [Table 1]

[0142]

[0143] In the table, the particle size indicates the number average particle size of the bubbles.

[0144] <Production Example of Binder Resin L>

[0145] Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: 72.0 parts by mass (0.20 parts by mole)

[0146] Terephthalic acid: 28.0 parts by mass (0.17 parts by mole)

[0147] Tin 2-ethylhexanoate (catalyst for esterification): 0.5 parts by mass

[0148] The above materials were weighed in a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. Then, the atmosphere in the flask was replaced with nitrogen, and the temperature was gradually raised with stirring. The reaction was caused to proceed at 200° C. for 3 hours while stirring.

[0149] Furthermore, the pressure in the reaction vessel was reduced to 8.3 kPa and maintained for 1 hour. Then, the temperature was cooled to 180° C. and the pressure was returned to atmospheric pressure.

[0150] Trimellitic anhydride: 1.3 parts by mass (0.01 parts by mole)

[0151] Tert-butylcatechol (polymerization inhibitor): 0.1 parts by mass

[0152] Then, the above materials were added, and the pressure in the reaction container was reduced to 8.3 kPa. The reaction was allowed to proceed for 1 hour while the temperature was maintained at 180° C. After confirming that the softening point measured in accordance with ASTM D36-86 reached 85° C., the temperature was lowered to stop the reaction, and a binder resin L was obtained.

[0153] <Production Example of Binder Resin H>

[0154] Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: 72.3 parts by mass (0.20 mol; 100.0 mol% of the total moles of the polyol)

[0155] Terephthalic acid: 18.3 parts by mass (0.11 mol; 65.0 mol% of the total moles of polycarboxylic acid)

[0156] Fumaric acid: 2.9 parts by mass (0.03 mol; 15.0 mol% of the total moles of polycarboxylic acid)

[0157] Tin 2-ethylhexanoate (catalyst for esterification): 0.5 parts by mass

[0158] The above materials were weighed in a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. Then, the atmosphere in the flask was replaced with nitrogen, and the temperature was gradually raised with stirring. The reaction was allowed to proceed at 200° C. for 2 hours while stirring.

[0159] Furthermore, the pressure in the reaction vessel was reduced to 8.3 kPa and maintained for 1 hour. Then, the temperature was cooled to 180° C. and the pressure was returned to atmospheric pressure.

[0160] Trimellitic anhydride: 6.5 parts by mass (0.03 mol; 20.0 mol% of the total moles of polycarboxylic acid)

[0161] Tert-butylcatechol (polymerization inhibitor): 0.1 parts by mass

[0162] Then, the above materials were added, and the pressure in the reaction container was reduced to 8.3 kPa. The reaction was allowed to proceed for 12 hours while the temperature was maintained at 160° C. After confirming that the softening point measured in accordance with ASTM D36-86 reached 132° C., the temperature was lowered to stop the reaction, and a binder resin H was obtained.

[0163] <Production of Pigment Dispersion 1>

[0164] Pigment (magenta pigment: Pigment Red 122): 35.0 parts by mass

[0165] Binder resin L: 65.0 parts by mass

[0166] UFB water 3: 5.0 parts by mass

[0167] A Henschel mixer (FM-75 manufactured by Nippon Coke & Engineering Co., Ltd.) was used for 20 s. -1 The above materials were mixed at a rotation speed of 1000 rpm for 5 minutes, and then kneaded at 120° C. using a twin-screw kneader (PCM-30 model manufactured by Ikegai Corporation) (step 1). The obtained kneaded product was cooled and coarsely pulverized using a grinder to a weight average particle size of 100 μm or less to obtain a coarsely pulverized product of pigment dispersion 1. The melt viscosity of binder resin L at 120° C. was 2080 Pa·sec.

[0168] <Production of Pigment Dispersions 2-9 and Comparative Pigment Dispersions 1-6>

[0169] Pigment dispersions 2 to 9 and comparative pigment dispersions 1 to 6 were obtained in the same manner as in pigment dispersion 1 except that the type and amount of UFB water were changed as shown in Table 2.

[0170] [Table 2]

[0171]

[0172] In the table, the parts are based on mass. "Parts relative to raw materials" shows the parts by mass of the binder resin and the dispersed material relative to 100.0 parts by mass in total.

[0173] <Production of finely pulverized product 1>

[0174] Binder resin L: 41.0 parts by mass

[0175] Binder resin H: 20.0 parts by mass

[0176] Pigment dispersion 1: 30.0 parts by mass

[0177] Synthetic wax 1 (hydrocarbon wax, peak temperature of maximum endothermic peak: 90° C.): 9.0 parts by mass

[0178] UFB water 1: 5.0 parts by mass

[0179] A Henschel mixer (FM-75 manufactured by Nippon Coke & Engineering Co., Ltd.) was used for 20 s. -1 The above materials were mixed at a rotation speed of 10000rpm for 5 minutes, and then kneaded using a twin-screw kneader (PCM-30 manufactured by Ikegai Corporation) (step 2). The kneaded product obtained was cooled and coarsely pulverized using a grinding mill to a weight average particle size of 100 μm or less to obtain a coarsely pulverized product 1.

[0180] A mechanical pulverizer (Turbo Mill T250-CRS, RS type rotor, manufactured by TurboKogyo Co., Ltd.) shown in the attached drawing was used, with a feed of 30 kg / h, a peripheral speed of 150 m / s, a gap of 1.0 mm between the rotor and the stator, a cooling air temperature of -10°C, and a cooling air volume of 10 m 3 The coarsely pulverized product 1 was pulverized under the condition of 1000 g / min to obtain a finely pulverized product 1.

[0181] <Production of Toner 1>

[0182] The finely pulverized product 1 is classified using a Coanda effect wind classifier ("Elbow JetLabo EJ-L3" manufactured by Nittetsu Mining Co., Ltd.) by adjusting various conditions such as the amount of injected air so that the target particle size and particle size distribution can be obtained, and the fine powder and the coarse powder are removed simultaneously to obtain toner particles.

[0183] To 100 parts by mass of the obtained toner particles, 1.8 parts by mass of a catalyst having a specific surface area of ​​200 m2 as measured by the BET method was added. 2 / g, silica fine particles treated with silicone oil for hydrophobicity, were mixed using a Henschel mixer (FM-75 manufactured by Nippon Coke & Engineering Co., Ltd.) for 30 s. -1 The resultant was mixed at a rotation number of 1000 for 10 minutes to obtain Toner 1. The weight average particle size (D4) of Toner 1 was 5.5 μm.

[0184] <Production Toners 2 to 15 and Comparative Toners 1 to 7>

[0185] Finely pulverized products 2 to 15 and comparative finely pulverized products 1 to 7 were obtained except that the kind and the amount of the additive materials including the binder resin and the pigment dispersion were changed as shown in Table 3 in the production of the toner 1, and the finely pulverized products were further classified in the same manner as in the production example of the finely pulverized product 1 and the toner 1 to obtain the toners 2 to 15 and comparative toners 1 to 7. As shown in Table 3, in the toners 5 to 14 and the comparative toners 1 to 6, the pigment dispersion was not used, but the binder resin and the pigment were used.

[0186] [Table 3]

[0187]

[0188] In the table, the parts are expressed by mass. "Parts relative to the raw material" means the parts by mass relative to 100.0 parts by mass of the total of the binder resin and the dispersed material.

[0189] <Production Example of Magnetic Carrier 1>

[0190] The magnetization intensity of magnetite 1 (1000 / 4π (kA / m) with a number average particle size of 0.30 μm is 65 Am 2 / kg)

[0191] Magnetite 2 with a number average particle size of 0.50 μm (1000 / 4π (kA / m) magnetic field has a magnetization intensity of 65 Am 2 / kg)

[0192] To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and each of the resultants was stirred at a high speed in a container at 100° C. or higher to process fine particles therein.

[0193] Phenol: 10% by mass

[0194] Formaldehyde solution: 6 mass% (40 mass% formaldehyde, 10 mass% methanol, and 50 mass% water)

[0195] Magnetite treated with the above silane compound 1: 58 mass%

[0196] Magnetite treated with the above silane compound 2: 26 mass%

[0197] 100 parts of the above materials, 5 parts of 28 mass % ammonia water, and 20 parts of water were added to a flask. While stirring and mixing the resultant, the temperature was raised to 85°C and maintained within 30 minutes. The polymerization reaction was allowed to proceed for 3 hours to solidify the generated phenolic resin. The solidified phenolic resin was then cooled to 30°C and additional water was added. Then, the supernatant was removed, the precipitate was washed with water, and then air-dried. Next, the resultant was vacuum dried (below 5 mmHg) at a temperature of 60°C to obtain a spherical magnetic carrier 1 dispersed with a magnetic body. The volume-based 50% particle size (D50) of the magnetic carrier 1 was 34.2 μm.

[0198] <Production Example of Two-Component Developer 1>

[0199] To 92.0 parts of the magnetic carrier 1 8.0 parts of the toner 1 were added and mixed using a V-type mixer (V-20 manufactured by Seishin Enterprise Co., Ltd.) to obtain a two-component developer 1 .

[0200] <Production Examples of Two-Component Developers 2 to 15 and Comparative Two-Component Developers 1 to 7>

[0201] Two-component developers 2 to 15 and comparative two-component developers 1 to 7 were each obtained by the same operation as in the production example of the two-component developer 1 except that the combination of toners in the developer was changed to each of Toners 2 to 15 and Comparative Toners 1 to 7.

[0202] <Example 1: Evaluation of Pigment Dispersion>

[0203] Using pigment dispersions 1 to 9 (Example 1) and comparative pigment dispersions 1 to 7 (Comparative Example 1), the amount of coarse particles of the pigment was evaluated by the following method.

[0204] <Evaluation Method of Dispersibility of Pigment in Pigment Dispersion>

[0205] The evaluation was performed by: forming a film of the pigment dispersion; observing the coarse particles of the pigment with an optical microscope; and then obtaining the number of coarse particles. First, 30 mg of the pigment dispersion was weighed, placed in a powder forming mold DD3015-0810 (NPaSYSTEM CO., LTD.), and pressed at a pressure of 20 MPa for 20 seconds using a small hot press (HC300-15 manufactured by ASONE Corporation), thereby preparing pellets of the pigment dispersion.

[0206] Next, the pellets were placed on an OHP film (VF-1420N, KOKUYO Co., Ltd.), and a NAFLON tape (TOMBO9001, NICHIAS Corporation) was placed thereon. The resultant was placed in a small heat press. After preheating at 150° C. for 1 minute and 30 seconds, the resultant was pressurized at 10 MPa for 1 minute. Thus, a film of the pigment dispersion was prepared.

[0207] When the film of the prepared pigment dispersion was observed with an optical microscope (VHX-5000, KEYENCE CORPORATION), it was observed that the elliptical pigment aggregates of about several microns to 100 microns were darker than the background color. The image of the pigment dispersion film with a field of view of 1.6 mm × 1.2 mm was obtained at a magnification of 300 times of the optical microscope. The number of coarse particles of the pigment above 2 μm observed in the obtained image was counted as the pigment dispersion index using the image processing software ImageJ, and evaluated according to the following criteria. The evaluation results are shown in Table 4.

[0208] (Evaluation Criteria)

[0209] A: The number of coarse particles of the pigment is less than 150

[0210] B: The number of coarse particles of the pigment is 150 or more and less than 200

[0211] C: The number of coarse particles of the pigment is 200 or more and less than 250

[0212] D: The number of coarse particles of the pigment is 250 or more and less than 300

[0213] E: The number of coarse particles of the pigment is 300 or more

[0214] [Table 4]

[0215]

[0216] <Example 2: Evaluation of Toner>

[0217] Toners 1 to 15 and Comparative Toners 1 to 7 were subjected to evaluation of pulverizability and evaluation of tinting strength.

[0218] <Evaluation of Toner Pulverizability>

[0219] When the particle size of the finely pulverized product prepared by pulverizing means under the same conditions is smaller, the pulverizability when producing the toner can be evaluated to be better. The weight average particle size (D4) of each finely pulverized product before obtaining toners 1 to 15 and comparative toners 1 to 7 was measured using the above-mentioned measurement method to obtain the particle size distribution of finely pulverized products 1 to 15 and comparative finely pulverized products 1 to 7. Evaluation was performed based on the weight average particle size (D4) and by the following criteria. The evaluation results are shown in Table 5.

[0220] <Evaluation Criteria>

[0221] A: Weight average particle size (D4) less than 5.20 μm

[0222] B: Weight average particle size (D4) is 5.20 μm or more and less than 5.40 μm

[0223] C: Weight average particle size (D4) is 5.40 μm or more and less than 5.60 μm

[0224] D: Weight average particle size (D4) is 5.60 μm or more

[0225] <Evaluation Method of Toner Coloring Strength>

[0226] A full-color copying machine imageRUNNER ADVANCE C5255 manufactured by Canon, Inc. was used as an image forming apparatus, and the evaluation was performed by loading the two-component developer 1 into the developing device of the magenta station.

[0227] The evaluation environment was set to normal temperature and humidity (23°C, 50% RH). Ordinary copy paper CS-068 (A4 paper, basis weight 68 g / m 2 , sold by Canon Marketing Japan Inc.) as evaluation paper.

[0228] First, in the above evaluation environment, an image output was produced under the condition that the developing bias voltage was fixed, and the image density of the output image was checked. The image density was measured using an X-Rite color reflection densitometer (500 series manufactured by X-Rite Corporation).

[0229] From the results of the X-Rite color reflection densitometer, the tinting power of the two-component developer 1 using the toner 1 was evaluated by the following criteria. Likewise, image outputs were produced using the two-component developers 2 to 15 using the toners 2 to 15 and the comparative toners 1 to 7 and the comparative two-component developers 1 to 7, respectively, and the tinting power was evaluated based on the measured image density and by the following criteria.

[0230] <Evaluation Criteria>

[0231] A: Image density is 1.85 or more

[0232] B: Image density is 1.75 or more and less than 1.85

[0233] C: Image density is 1.65 or more and less than 1.75

[0234] D: Image density is 1.55 or more and less than 1.65

[0235] E: Image density less than 1.55

[0236] [Table 5]

[0237]

[0238] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.

Claims

1. A method for producing a toner, the method comprising: A melt-kneading step of melt-kneading a mixture A comprising a binder resin and a dispersed material relative to the binder resin to obtain a kneaded product, wherein: The mixture A contains 1.0 to 10.0 parts by mass of water relative to 100.0 parts by mass of the binder resin and the dispersed material in total, The water contained in the mixture A contains bubbles including ultrafine bubbles having a particle size of 1000 nm or less, and The number of the ultrafine bubbles contained in the water contained in the mixture A is 1.0×10 4 More than one.

2. The method for producing a toner according to claim 1, wherein The method includes the step of pulverizing the kneaded product.

3. The method for producing a toner according to claim 1 or 2, wherein The dispersed material contains a release agent.

4. The method for producing a toner according to claim 1 or 2, wherein The dispersed material includes a pigment.

5. The method for producing a toner according to claim 1 or 2, wherein The dispersed material includes a pigment and a release agent.

6. The method for producing a toner according to claim 1 or 2, wherein The mixture A contains 2.0 to 8.0 parts by mass of water relative to 100.0 parts by mass in total of the binder resin and the dispersed material.

7. The method for producing a toner according to claim 1 or 2, wherein The number average particle size of the bubbles is 1000 nm or less.

8. The method for producing a toner according to claim 1 or 2, wherein The number average particle size of the bubbles is 700 nm or less.

9. The method for producing a toner according to claim 4, wherein The melt-kneading step is a first melt-kneading step of melt-kneading a first mixture containing a part of the binder resin and at least a part of the pigment to obtain a first kneaded product, The first mixture is mixture A, and The method includes a second melt-kneading step of melt-kneading a second mixture containing at least the first kneaded product and the remaining binder resin after the first melt-kneading step.

10. The method for producing a toner according to claim 9, wherein The second mixture contains 1.0 to 10.0 parts by mass of water relative to a total of 100.0 parts by mass of the binder resin and the dispersed material in the second mixture. The water contained in the second mixture contains bubbles including ultrafine bubbles having a particle size of 1000 nm or less, and The number of ultrafine bubbles contained in the water contained in the second mixture is 1.0×10 4 More than one.

Citation Information

Patent Citations

  • Toner and method for manufacturing toner

    JP2002072554A

  • Toner, its making method, developer, and method and apparatus for forming image

    JP2003098739A

  • Method of manufacturing color toner and color toner

    JP2005352131A

  • Electrophotographic toner

    JP2008191491A

  • Powder particle thermal treatment apparatus and toner manufacturing method

    JP2013020244A